Infectious complications in children treated for hodgkin and non-hodgkin lymphomas in polish pediatric leukemia/lymphoma study group: incidence, epidemiology and etiology. Issue 1 (2nd January 2019) - Zajac-Spychala, Olga; Wachowiak, Jacek; Szmydki-Baran, Anna; Hutnik, Lukasz; Salamonowicz, Malgorzata; Matysiak, Michal; Czyzewski, Krzysztof; Wysocki, Mariusz; Zalas-Wiecek, Patrycja; Malas, Zofia; Badowska, Wanda; Gryniewicz-Kwiatkowska, Olga; et al.
Abstract: The objective of this nation-wide study was to evaluate the epidemiology and profile of bacterial (BI), viral (VI), and invasive fungal disease (IFD) in patients treated for non-Hodgkin lymphoma (NHL) and Hodgkin lymphoma (HL) between the years 2013–2015. In the analyzed period of time, within the studied group of 328 children diagnosed and treated for lymphomas, at least one infectious complication (IC) was diagnosed i.e. 39.3% children. In these patients there were 350 episodes of IC, therein 80.6% episodes of BI, 11.1% episodes of VI, and 8.3% episodes of IFD. In both groups, NHL and HL patients, a stable level of bacterial infections, with an increase in resistance rates, and increased levels of viral and fungal infections were observed. Profile of BI does not depend on lymphoma type, with predominance of Gram-negative bacteria and higher prevalence of MDR pathogens. The overall survival of lymphoma patients with IC was comparable for different types of infections.